Effects of Simulated Heat Wave on Oxidative Physiology and Immunity in Asian Yellow Pond Turtle (Mauremys mutica) - Li, Shuran; Li, Jinhuan; Chen, Wei; Xu, Zhiwang; Xie, Lei; Zhang, Yongpu (Frontiers in Ecology and Evolution, 2021)
Global warming has led to an increase in the frequency, duration, and intensity of heat waves in the summer, which can cause frequent and acute heat stress on ectotherms. Thus, determining how ectothermic animals respond to heat waves has been attracting growing interest among ecologists. However, the physiological and biochemical responses to heat waves in reptiles, especially aquatic reptiles, are still poorly understood. The current study investigated the oxidant physiology, immunity, and expression levels of heat shock proteins (HSP) mRNA after exposure to a simulated heat wave (one week, 35 ± 4℃), followed by a recovery period (one week, 28 ± 4 °C) in juvenile Asian yellow pond turtle (Mauremys mutica), a widely farmed aquatic turtle in East Asia. The contents of malondialdehyde (MDA) in the liver and muscle were not significantly affected by the heat wave or recovery. Of all antioxidant enzymes, only the activity of glutathione peroxidase (GSH-Px) in muscles increased after heat wave, while the total superoxide dismutase (T-SOD), catalase activity (CAT), and total antioxidant capacity (T-AOC) did not change during the study. The organo-somatic index for the liver and spleen of M. mutica decreased after the heat wave but increased to the initial level after recovery. In contrast, plasma lysozyme activity and serum complement C4 levels increased after the heat wave, returning to the control level after recovery. In addition, heat waves did not alter the relative expression of HSP60, HSP70, and HSP90 mRNA in the liver. Eventually, heat wave slightly increased the IBR/n index. Therefore, our results suggested that heat waves did not lead to oxidative damage to lipids in M. mutica, but deleteriously affected the turtles’ immune organs. Meanwhile, the constitutive levels of most antioxidative enzyme activities, HSPs and enhanced blood immune functions might protect the turtles from the threat of heat waves under the current climate scenarios.